EFFECT OF DIFFERENT CONCENTRATIONS OF BOVINE SERUM ALBUMIN ON IN VITRO MATURATION OF BUFFALO OOCYTES - MISTRY, C N; DHAMI, A J; SUTHAR, V S; RANK, D N; JOSHl, C G (The Indian Journal of Animal Reproduction, 2010)
A total of 456 fresh ovaries of Surti buffaloes without CL were obtained from the local abattoir. By :;!icing metl 10d of 1409 oocytes were recovered with an average of 3 .09 oocytes per ovary. The average recovery rate of grade A, Band C oocyte were 1.02, 1.22 and 0.85, respectively. The overall maturation rate with 0.05, 0.1, 0.3, 0.6 and 0.9 per cent concentration of BSA (Sigma) in TCM"199 medium supplemented with 10 IU/ml of eCG and 5 IU/ml of hCG was found to be 44.52, 50.99, 59.02, 84.43 and 64.29 per cent (P<0.01 ), respectively. The highest maturation rate (90.00 %) of grade A oocytes was found in BSA 0.6 % followed by BSA 0.05 % (73.91 %), while in grade Bit was in BSA 0.9 % (86.09 %) followed by BSA 0.6 % (82.61 %), and for grade C oocytes the highest maturation rate was with BSA 0.6 % (80.56 %) followed by BSA 0.9 % 60.53 %). According to nuclear maturation (using Hoechst 33342 stain), the highest percentage of oocytes wlth germinal vesicle was found in medium containing BSA 0.3 % (15.57 %) followed closely by others, except in BSA 0.6 % (4.92 %). The highest percentage of oocytes with broken germinal vesicle (GVBD) was found in BSA 0.9 % (28.57 %), which did not differ from other concentrations. The higher percentage of oocytes with Metaphase- 1 and-II were in the medium containing BSA 0.6 % (22.13 and 35.25 %) followed by BSA 0.9 % (15.87 and 19.84 %), and the least in BSA 0.05 and 0.1 percent concent;ations. The percentage of degenerated oocytes decreased with increase in BSA concentration from 0.05 to 0.6 per cent (40.41 to 10.67 % ), except that in BSA 0.9 % it was 3.02 per cent. The results clearly showed that BSA@ 0.6 per cent in TCM-199 medium supplemented with 10 IU/ml of eCG and 5 IU/ml of hCG is ideal over other concentrations of BSA for in vitro maturation of buffalo follicular oocytes.